Gamifying Career Guidance: A Quasi-Experimental Study Using the Career Snakes and Ladders Game - Putu Agus Indrawan; Katharina EP Korohama; Al Ihzan Tajuddin (Bisma The Journal of Counseling, 2025)
Career awareness among junior high school students remains low due to the lack of interactive and engaging guidance approaches. Conventional lecture-based career counseling often fails to spark student interest or encourage meaningful reflection about their future. This study aims to evaluate the effectiveness of the Career Snakes and Ladders Simulation Game as a group guidance medium to enhance career awareness. A quantitative experimental method with a quasi-experimental design was employed. The sample consisted of 20 eighth-grade students divided into experimental and control groups. The experimental group participated in a one-hour simulation game session, while the control group received traditional lecture-based guidance. Data were collected using a validated Career Awareness Questionnaire and analyzed using the Mann-Whitney U test. Results showed a significant improvement in the experimental group (p = 0.001) with a large effect size (Cohen’s d = 2.543). The game proved effective as a medium to increase students’ career awareness through movement-based, interactive, and engaging strategies. The findings imply that game-based approaches can serve as a strategic alternative in guidance and counseling services, particularly within the context of innovative and enjoyable career counseling models.